1999
DOI: 10.1182/blood.v94.2.550
|View full text |Cite
|
Sign up to set email alerts
|

The Glucocorticoid Receptor Cooperates With the Erythropoietin Receptor and c-Kit to Enhance and Sustain Proliferation of Erythroid Progenitors In Vitro

Abstract: Although erythropoietin (Epo) is essential for the production of mature red blood cells, the cooperation with other factors is required for a proper balance between progenitor proliferation and differentiation. In avian erythroid progenitors, steroid hormones cooperate with tyrosine kinase receptors to induce renewal of erythroid progenitors. We examined the role of corticosteroids in the in vitro expansion of primary human erythroid cells in liquid cultures and colony assays. Dexamethasone (Dex), a synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(90 citation statements)
references
References 47 publications
1
88
0
1
Order By: Relevance
“…The development of culture techniques, defined by us as human erythroid massive amplification (HEMA) cultures, which produce large numbers of cultured RBCs (cRBCs),10‐14 allowed studies that demonstrate that CD34 pos cells from various sources generate ex vivo great numbers of erythroblasts (ERYs) that mature into functional RBCs . A subsequent study demonstrated that autologous cRBCs generated by mobilized CD34 pos cells survive in vivo as long as their natural counterpart, providing the proof of concept that cRBCs may be used for transfusion .…”
mentioning
confidence: 99%
“…The development of culture techniques, defined by us as human erythroid massive amplification (HEMA) cultures, which produce large numbers of cultured RBCs (cRBCs),10‐14 allowed studies that demonstrate that CD34 pos cells from various sources generate ex vivo great numbers of erythroblasts (ERYs) that mature into functional RBCs . A subsequent study demonstrated that autologous cRBCs generated by mobilized CD34 pos cells survive in vivo as long as their natural counterpart, providing the proof of concept that cRBCs may be used for transfusion .…”
mentioning
confidence: 99%
“…This development is controlled by multiple growth factors, the two most important being the glycoproteins EPO and SCF [33,34]. A variety of other factors, such as insulin‐like growth factor 1, transforming growth factor‐ß and glucocorticoids, have been proposed to have a supportive effect on human RBC development [35–37]. However, despite this increasing knowledge about soluble factors influencing erythropoiesis, little is known about the impact of stromal cells and various ECM proteins on erythropoiesis and whether these factors may arrest or induce the lineage‐committed maturation of HSCs into RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of stress such as erythrolysis or hypoxia, rapid expansion of erythroid precursors is achieved in vivo by what is defined as “stress erythropoiesis.” Mimicking stress erythropoiesis, erythroid precursors can be expanded in vitro by activation of the glucocorticoid receptor [65, 66]. Along with SCF, EPO, and insulin‐like growth factor I, a glucocorticoid receptor agonist such as dexamethasone has been shown to induce proliferation of erythroid precursors on the order of 10 5 to 10 6 [66, 67]. Even with better protocols, the amplification fold of CB‐derived erythroid precursors is restricted to <10 10 ‐fold [66].…”
Section: Ex Vivo Production Of Human Rbcsmentioning
confidence: 99%